AGREEMENT OF MELBOURNE RAPID FIELDS PERIMETRY PARAMETERS TO HUMPHREY FIELD ANALYZER IN MODERATE-SEVERE GLAUCOMA PATIENTS: RELATIONSHIP BETWEEN VISUAL ACUITY AND MELBOURNE RAPID FIELDS ACCURACY: Oral Presentation - Observational Study - Resident - Mayasari, Yuri Dwi; Oktariana, Virna Dwi; Fitriani, Dewi Yunia (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesPerimetric examination is vital for measuring visual field defects and predicting the progression ofglaucoma. The Covid-19 pandemic prompted the use of perimetry at home. Tablet or website-basedperimetry becomes an option due to unavailability of Humphrey Field Analyzer (HFA). MelbourneRapid Fields (MRF) is affordable, portable and reliable, even provide the same benefits as HFA. Thisstudy aimed to assess the agreement of MRF results to HFA in moderate-severe glaucoma patientswith impaired visual acuity. MethodsObservational study using a cross-sectional design to assess the relationship between visual acuityand the agreement of MRF vs HFA in moderate-severe glaucoma patients. Subjects were groupedinto two groups based on visual acuity. Each subject was examined with MRF and HFA, the order ofexamination was randomized using block randomization. ResultsThe test durations were shorter on MRF than HFA (265.7±26.6 vs 384.4±46.7, P<0.001). There wasno significant difference in the reliability index of the two perimetry. MRF showed a high level ofconcordance in its outcomes with HFA (R=0.931, intraclass correlation coefficient (ICC)=0.957 formean defect (MD) and R=0.941, ICC=0.974 for Visual Field Index (VFI)). MRF also showed levels oftest-retest repeatability comparable to HFA (R=0.948, ICC=0.989 for MD and R=0.946, ICC=0.989for Visual Capacity (VC)). There was no correlation between visual acuity and MRF accuracy,p>0.05. ConclusionThe perimetry results from MRF have a very stong correlation to the HFA outcomes. MRF also hastest-retest repeatability comparable to HFA. The accuracy of the MRF results does not correlate withvisual acuity.